Differences in nutrient and undesirable substance concentrations in Maurolicus muelleri across the Bay of Biscay, Norwegian fjords, and the North Sea - Zhu, Yiou; Azad, Atabak Mahjour; Kjellevold, Marian; Bald, Carlos; Iñarra, Bruno; Alvarez, Paula; Boyra, Guillermo; Berntssen, Marc; Madsen, Lise; Wiech, Martin (Frontiers in Marine Science, 2023)
Introduction We are having pressing issues of global food insecurity and malnutrition. Mesopelagic communities in the North Atlantic have been estimated to have high biomasses of organisms. Some of these low-trophic organisms are known to be nutrient-dense and may thus contribute to food security and nutrition. Here, we aim to understand the variation in nutrient and undesirable substance concentrations in a common mesopelagic species, Maurolicus muelleri in the North Atlantic Ocean. Methods We sampled the M. muelleri from the Bay of Biscay (BB), Norwegian fjords (NF), and the North Sea (NS). The concentrations of micro- and macronutrients, undesirable metals, and persistent organic pollutants (POPs) were measured in composite whole fish samples. Results We found no difference across the sampling areas in the selected micronutrients except that the NF and NS samples had higher vitamin A1 concentrations than the BB samples. The NF samples had higher concentrations of fat, fatty acids, and POPs but lower concentrations of cadmium than the BB and NS samples; the differences in fat and fatty acids were only marginal in the NF-BB pair. The BB samples had lower arsenic concentrations than the NS samples, and lower concentrations of erucic acid and mercury than the NF and NS samples. Comparing the measured values against existing EU regulation values for nutrients and undesirable substances for human consumption, we found that the samples from NS and BB may cause food safety concerns due to their high cadmium concentrations, while the M. muelleri from all the sampling areas are qualified as good sources of iron, selenium, vitamin A1, and ω-3 fatty acids. Discussion This study confirms that M. muelleri from the North Atlantic Ocean may play an important role in food security and nutrition. However, potential variations in nutrient and undesirable substance concentrations related to seasonality, fish body size, and maturity level shall be taken into consideration prior to exploiting such a marine resource. Further understanding of trophic ecology, life cycles, and productivity of M. muelleri is essential to investigate the drivers behind the observed variation in nutrient and undesirable substance concentrations.